Theoretical Study on the Sensing Mechanism of Novel Hydrazine Sensor TAPHP and Its ESIPT and ICT Processes - Liu, Songsong; Lu, Jiajun; Lu, Qi; Fan, Jianzhong; Lin, Lili; Wang, Chuankui; Song, Yuzhi (Frontiers in Chemistry, 2020)
The photophysical and photochemical properties of the novel hydrazine sensor TAPHP and the TAPDP generated by the cyclization reaction of TAPHP with hydrazine are investigated using the density functional theory and time-dependent density functional theory. The results show that both the excited-state intramolecular proton transfer and intramolecular charge transfer can occur for TAPHP and TAPDP. Analysis of bond parameters and infrared vibrational spectra indicate that hydrogen bonds are enhanced in the first excited state, which is beneficial to excited-state intramolecular proton transfer. The strength of hydrogen bonds is also visualized by using the independent gradient model and topological analysis. The core-valence bifurcation index and bond critical point parameters are further employed to measure hydrogen bonds. The reaction path of proton transfer is obtained through the potential energy curves. The excitation of TAPHP and TAPDP is attributed to the charge transfer excitation, which is determined by the characteristics of the hole-electron distribution. In addition, the absorption and fluorescence spectra agree well with the experimental results, confirming that TAPHP is an excellent sensor of hydrazine.